Entrepreneurial Orientation and Performance of Small Business in Vryburg Region North West Province South Africa - Oni, Olabanji; Agbobli, Edem Korku; Iwu, Chux Gervase (Journal of Reviews on Global Economics, 2019)
Small businesses play a significant role in job creation, economic growth and development, innovation, competitiveness and poverty alleviation that eventually improve business performance. The purpose of this study was to assess the association between Entrepreneurial orientation (EO) (innovativeness, risk taking, proactiveness and autonomy) and performance of small business in Vryburg area North West Province South Africa(SA). This quantitative study utilised questionnaire for data collection in a survey. The population were small business owners/managers in North West Province South Africa. Simple random sampling method was utilised to obtain participants for the study. The study utilised descriptive and inferential statistics. The result shows that only three attributes (innovativeness, risk taking and proactiveness) influence business performance while no association was found between autonomy and business performance. Additionally, positive relationship exists between the overall EO and the performance of small business. Empirically, the study contributes to the literature on EO and advance recommendations to improve the EO of small business in South Africa. The study recommends that policy makers, owners and managers of small business strategize on enterprise development and better business performance of small business in Vryburg area North West Province South Africa.